Comparative study of non-standard power diodes - Tan, Cher Ming (2010)
Various non-standard power diode structures have been proposed which are superior in performance in comparison to the standard power diode. However, each of these structures help optimize certain electrical parameters with corresponding trade-offs for others. In this work, the electrical parameters of three non-standard diode structures viz. SPEED diode, BUFFER diode and CLC (Carrier Lifetime Control) diode are evaluated in comparison to those of the conventional P+NN+ standard diode. A Design of Experiment (DOE) combined with extensive MEDICI simulation is performed, followed by Response Surface Methodology (RSM) to empirically relate the electrical parameters with the diode structural and doping parameters. A